Citocinas e quimiocinas como biomarcadores terapêuticos na depressão: revisão sistemática e meta-análise - Freitas, Thiago Holanda (2017)
Inflammatory Cytokines and chemokines as response biomarkers in major depression. Mounting evidence suggests that aberrations in immune-inflammatory pathways contribute to the pathophysiology of major depressive disorder (MDD), and individuals with MDD may have elevated levels of predominantly pro-inflammatory cytokines and C-reactive protein. In addition, previous meta-analyses suggest that antidepressant drug treatment may decrease peripheral levels of interleukin-1 beta (IL-1β) and IL-6. Recently, several new studies examining the effect of antidepressants on these cytokines have been published, and so we performed an up-dated meta-analysis of studies that measured peripheral levels of cytokines and chemokines during antidepressant treatment in patients with MDD. The PubMed/MEDLINE, EMBASE, and PsycInfo databases were searched from inception through March 9th, 2017. Forty-five studies met inclusion criteria (N=1517). Peripheral levels of IL-6, tumor necrosis factor alpha (TNF-α), IL-1β, IL-10, IL-2, IL-4, interferon-γ, IL-8, the C-C motif ligand 2 chemokine (CCL-2), CCL-3, IL-1 receptor antagonist, IL-13, IL-17, IL-5, IL-7, and the soluble IL-2 receptor were measured in at least three datasets and thus were meta-analyzed. Antidepressant treatment significantly decreased peripheral levels of IL-6 (Hedges g = -0.454, P < 0.001), TNF-α (g = -0.202), IL-10 (g = -0.566), and CCL-2 (g = -1.502). These findings indicate that antidepressants decrease several markers of peripheral inflammation. However, this meta-analysis did not provide evidence that reductions in peripheral inflammation are associated with antidepressant treatment response although few studies provided separate data for treatment responders and non-responders.